The accursed share an essay on general economy - Bataille, Georges 1897-1962 (Zone Books, 1993)
Most Anglo-American readers know Bataille as a novelist. The "Accursed Share "provides an excellent introduction to Bataille the philosopher. Here he uses his unique economic theory as the basis for an incisive inquiry into the very nature of civilization. Unlike conventional economic models based on notions of scarcity, Bataille's theory develops the concept of excess: a civilization, he argues, reveals its order most clearly in the treatment of its surplus energy. The result is a brilliant blend of ethics, aesthetics, and cultural anthropology that challenges both mainstream economics and ethnology. The three volumes of "The Accursed Share" address what Georges Bataille sees as the paradox of utility: namely, if being useful means serving a further end, then the ultimate end of utility can only be uselessness. The first volume, the only one published before Bataille's death, treated this paradox in economic terms, showing that "it is not necessity but its contrary, luxury that presents living matter and mankind with their fundamental problems." In the second and third volumes, "The History of Eroticism" and "Sovereignty", Bataille explores the same paradox of utility from an anthropological and an ethical perspective, respectively. "The History of Eroticism" analyzes the fears and fascination, the prohibitions and transgressions attached to the realm of eroticism as so many expressions of the "uselessness" of erotic life. In the third volume, Bataille raises the ethical problems of sovereignty, of "the independence of man relative to useful ends."